DAYA KECAMBAH BENIH SAWI (Brassica juncea) DAN CABAI RAWIT (Capsicum frutescens L) DENGAN APLIKASI PUPUK HAYATI PGPR (Plant Growth Promoting Rhizobacteria) - Hilwa Walida (JURNAL AGROPLASMA, 2019)
Growth and productivity of the plant was begun with germination process. If the seed did not have a good germination process, it would affect to the growth and yield of the plant. The aim of this study was to determine the effect of PGPR application as biological fertilizer on the spourt power and the germination rate of mustard and chili pepper. This research was conducted by dissolving 50 g of PGPR Rhizomax in 5 liters of water. The seeds of chili pepper and mustard were soaked into the PGPR solution as treatment and into water as control. They were soaked for 2 hours to chili pepper seeds and 15 minutes to the mustard seeds. Each treatment consisted of 50 seeds. Spinning time test were limited to 2 weeks in chili pepper seeds and 4 days in the mustard seeds. Percentage of germination daily of mustard seeds showed significant increase on 3rd day and the chili pepper seeds on the 8th day. The sprout power on control were only 40% in the chili seeds and 80% in the mustard seeds, but with PGPR application, they were 90%. The germination rate of mustard seeds in control and PGPR application were the same in 3rd day, but in chili pepper seeds, they were on the 9th day by using PGPR and 11th day in control. Keywords: The Sprout Power, The Germination Rate, PGPR Application